TRANSPLANTATION OF ADIPOSE TISSUE AS A REPLACEMENT THERAPY - V. G. Ablamunits; S. E. Klebanov (Вестник трансплантологии и искусственных органов)
Transplantation of endocrine organs and tissues is often considered as an alternative therapy which has a number of advantages compared to regular injections for replacement of a missing hormone or another factor. During the last two decades, accumulating evidence demonstrates that adipose tissue is an endocrine organ that plays a pivotal role in the key physiological processes, and this raises a possibility of its potential use in transplantations aimed to correct inborn metabolic defi ciencies. In this review, we provide examples of the factors, secreted by adipose tissue, and which may be responsible for particular human pathologies when missing. We discuss practical aspects of fat transplantation, such as availability of donor tissue, its susceptibility to rejection, rationality of immune suppression, and possible ways to achieve medication-free tolerance.